To The West - Fenn, George Manville, 1831-1909; Morgan, Walter Jenks, 1847-1924 (Salt Lake City, UT : Project Gutenberg, 2007)
"To The West" by George Manville Fenn is a novel written in the late 19th century. The story follows two young clerks, Mayne Gordon and his colleague Esau Dean, who work under a tyrannical auctioneer, Mr. Isaac Dempster. Dissatisfied with their oppressive working conditions, they decide to venture to British Columbia in search of new opportunities and adventures, particularly in gold prospecting, where they anticipate facing various characters and challenges along their journey. At the start of the narrative, the opening chapters introduce the boys' difficult working environment under Mr. Dempster, illustrating his cruel and abusive nature towards them. As the story unfolds, Mayne becomes increasingly affected by the harshness of their situation, while Esau frequently contemplates a more adventurous life in the military. The narrative takes a thrilling turn when the boys unite against their employer's mistreatment, culminating in a physical altercation that leads to their arrest. Following their release, they explore the possibility of emigrating to the untamed lands of British Columbia to seize a brighter future, igniting a sense of excitement and hope for what lies ahead. (This is an automatically generated summary.)
Release date is 2007-05-16
Produced by Nick Hodson of London, England
Keywords: Frontier and pioneer life -- British Columbia -- Juvenile fiction; Canada -- Emigration and immigration -- Juvenile fiction; British Columbia -- Gold discoveries -- Juvenile fiction